Molecular Characterisation of α‐ and β‐Thalassaemia among Indigenous Senoi Orang Asli Communities in Peninsular Malaysia. (16th June 2017) - Koh, Danny Xuan Rong; Raja Sabudin, Raja Zahratul Azma; Mohd Yusoff, Malisa; Hussin, Noor Hamidah; Ahmad, Rahimah; Othman, Ainoon; Ismail, Endom
Summary: Thalassaemia is a public health problem in Malaysia, with each ethnic group having their own common mutations. However, there is a lack on data on the prevalence and common mutations among the indigenous people. This cross‐sectional study was performed to determine the common mutations of α ‐ and β ‐thalassaemia among the subethnic groups of Senoi, the largest Orang Asli group in Peninsular Malaysia. Blood samples collected from six Senoi subethnic groups were analysed for full blood count and haemoglobin analysis (HbAn). Samples with abnormal findings were then screened for α‐ and β ‐globin gene mutations. Out of the 752 samples collected, 255 showed abnormal HbAn results, and 122 cases showing abnormal red cell indices with normal HbAn findings were subjected to molecular screening. DNA analysis revealed a mixture of α‐ and β ‐globin gene mutations with 25 concomitant cases. The types of gene abnormalities detected for α‐ thalassaemia were termination codon (T>C) Hb CS ( α CS α ), Cd59 (G>A) haemoglobin Adana (Hb Adana) ( α Cd59 α ), initiation codon (ATG>A‐G) ( α IniCd α ), two‐gene deletion ( – SEA ), and single‐gene 3.7‐kb deletion ( ‐α 3.7 ). For β ‐thalassaemia, there were Cd26 (G>A) Hb E ( β E ), Cd19 (A>G) Haemoglobin Malay (Hb Malay) ( β Cd19 ), and IVS 1–5 (G>C) ( β IVS 1–5 ).